Posisi Pendidikan Islam Dan Pengaruhnya Pada Isu Multikulturalisme - Sawaty, Ikhwan (-, 2025)
Islamic education holds a strategic position in shaping individuals' mindsets and character within an increasingly diverse society. This study aims to analyze the role of Islamic education in addressing multiculturalism, particularly in the context of cultural, religious, and ethnic diversity in Indonesia. This research employs a qualitative approach through an in-depth literature review of relevant studies on Islamic education and multiculturalism. The findings indicate that Islamic education, with its principles of universality and inclusivity, serves as an effective instrument in instilling values of tolerance, respect for differences, and social harmony. However, its implementation still faces challenges, such as exclusivism and interpretative bias. In conclusion, Islamic education must continue to adapt to play a significant role in building a multicultural, inclusive, and harmonious society. This study emphasizes the importance of strengthening the integration of multicultural values into the Islamic education curriculum.